Derivative-Free Characterizations of Q_K Spaces II - Li, Songxiao; Wulan, Hasi (Sarajevo Journal of Mathematics, 2024)
The Q_K spaces on the open unit disk are characterized by some oscillations in the Bergman metric without the use of derivatives. Our results are new even in the case of Q_p spaces. 2000 Mathematics Subject Classification. 30H05, 46E15